Technical drawing for fashion - Szkutnicka, Basia (London : Laurence King, 2010)
Shows how to create a technical fashion drawing using a step-by-step method that is explained for those who wish to use Adobe Illustrator as well as for those who prefer to draw by hand. This book presents over 250 technical drawings of garment types, styles and construction details, and the basic key shapes.
boek